STRATEGI ORGANISASI PEREANGKAT DAERAH DALAM MENGURANGI TINGKAT PENGANGGURAN DI KABUPATEN KUDUS - Intan Damayanti; Ahmad Taufiq (Journal of Politic and Government Studies, 2018)
Unemployment problem is a classical problem faced by the local government with no exception for Kudus Regency. The local Government of Kudus Regency has technical management unit of the vocational training center with many advantages compared to training center in the surrounding regency. In 2014, up taking level of training participants go up 11,25 % from 49,12 % to 60,37 %, so it has implications on decreasing unemployment 3,04 %. However, in 2015 up taking level of training participants decrease to 43,32 % and open unemployment level get up even if only 0,1% from 5,03 % to 5,04 %. This data show there is paradox, unemployment level in surrounding Regency decrease but in Kudus Regency precisely increase. Kudus regency through Technical Implementation Unit of Training Center (UPTD BLK) also implement 3 in 1 program form Ministry of Employment for revitalization training center but until 2017 that program run into stagnation. Therefore, this research intend to analyze management of UPTD BLK for realize objective of Local Government to decrease unemployment and the factors can affect implementation 3 in 1 program. This research use natural qualitative method with observation, interview, and documentation technique then presented through analyze and interpret data. The result of research show open unemployment level in Kudus Regency fluctuate because it is brought on inconsistent performance from UPTD BLK Kudus Regency. It occur because short of alignment between planning, coaching, organizing, until monitoring. While the instability because of UPTD BLK in Kudus Regency doesn’t has visionable and concrete objective, there is no principle of good governance are excecuted, there is no road map the startegical are formed to carry out 3 in 1 program maximally. Based on this research show if performance management is undertaken carelessly, too flexible, and it doesn’t has vision in the future so it aren’t growth wellKeywords: UPTD BLK, Unemployment, Public Management